Eosinophilic pancreatitis: a review of the pathophysiology, diagnosis, and treatment. (12th December 2020) - Sun, Yue; Pan, Dan; Kang, Kai; Sun, Ming-Jun; Li, Yi-Ling; Sang, Li-Xuan; Chang, Bing
Abstract: Eosinophilic pancreatitis (EP) is an extremely rare disease caused by purely eosinophilic infiltration of the pancreas. EP is prone to being misdiagnosed as pancreatic cancer, causing unnecessary economic and physical harm to the patient. We report three cases of EP that were cured by steroids without relapse from 2017 to now. The clinical data of the three patients, including clinical manifestations, serological manifestations, imaging (ultrasound, computed tomography, and MRI), pathological diagnosis and treatment, and telephone follow-up of all patients, were retrospectively analysed. In addition, a literature search was conducted on the Web of Science and PubMed databases using key terms related to EP, considering case reports with no restrictions on the date of publication or language. In conclusion, we analysed 19 cases and determined the diagnostic criteria for EP. The diagnostic algorithm for EP can be used to diagnose EP easily. We hope that our standards and algorithm can reduce the rate of misdiagnosis and contribute to clinical diagnosis and treatment. In addition, we expect to evaluate more EP cases to test our diagnostic criteria and design a systematic diagnostic flow chart.